2018
DOI: 10.31234/osf.io/7rmu6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Investigation of the Divergences and Convergences of Trait Empathy across Two Cultures

Abstract: 1 Cross-Cultural Approach to Empathy Authors Biographical Note:Parvaneh Yaghoubi Jmai is a doctoral student in Educational Psychology and Educational Neuroscience at the University of Alabama. Her research interests include cultural differences in empathic behavior, personality and social development in adolescence, social neuroscience, and personality assessment. She is currently working on neural correlates of people's empathetic responses in social settings and evaluating the psychometric properties of psyc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…For example, in some western cultures like the United States, it is culturally normative to define oneself as independent from others (i.e., an individualistic culture), whereas in other cultures it is culturally normative to define yourself in terms of your relationships with other people (i.e., a collectivist culture; Markus & Kitayama, 1991). People from collectivist cultures are higher in trait empathy, prosocial behavior, empathic concern, and perspective taking (Chopik et al, 2017;Yaghoubi Jami et al, 2019). Thus, although uncertain, the effects of empathy on the interpretation of everyday rules may differ for persons from individualistic versus collectivist cultures.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…For example, in some western cultures like the United States, it is culturally normative to define oneself as independent from others (i.e., an individualistic culture), whereas in other cultures it is culturally normative to define yourself in terms of your relationships with other people (i.e., a collectivist culture; Markus & Kitayama, 1991). People from collectivist cultures are higher in trait empathy, prosocial behavior, empathic concern, and perspective taking (Chopik et al, 2017;Yaghoubi Jami et al, 2019). Thus, although uncertain, the effects of empathy on the interpretation of everyday rules may differ for persons from individualistic versus collectivist cultures.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…The current study differs from previous studies in three ways. First, culture is a multidimensional construct ( Jami et al, 2018 ); nevertheless, in previous Western–Asian cross-cultural studies of self-report empathy, the participant culture was identified only according to a single aspect, such as, nationality (e.g., Kaelber and Schwartz, 2014 ), ethnicity (e.g., Xu et al, 2009 ), or country of birth and growing up (e.g., Cassels et al, 2010 ). With reference to both the definition of culture and these previous studies, culture is defined as a string of simple proxies in the current study, including nationality (Australians or Mainland Chinese), ethnicity (Caucasians or Han Chinese), and country of birth and main place of growing up (Australian and Mainland China).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies examine empathy in multicultural settings, but very few focus on the Asian context (Jami et al, 2019). With relevance to culture, Hofstede's work on culture has been widely used to comprehend cultures across communities in the world, using concepts such as 'individualism' and 'collectivism' (Jami et al, 2019), and there is a growing need for collaboration between the West and East to understand multiculturalism (Marovic, 2020).…”
Section: Empathy In Multicultural Settingsmentioning
confidence: 99%